A personal and poetic inquiry into Dutch coloniality - Berends, Joel E. (UI Scholars Hub, 2023)
The following personal and poetic inquiry examines Indonesian objects, art, and cultural expressions through the lensing of coloniality (A. Benítez Rojo 1992; A. Quijano and M. Ennis 2000; W.D. Mignolo 2011). The inquiry interacts with the objects, art, and cultural expressions through the creation of ekphrastic poetry – poems which describe works of art. Specifically, this inquiry examines my experiences with Dutch coloniality as a white cisgendered man with a Dutch heritage/inheritance who was born and raised in a predominantly Dutch immigrant community in West Michigan in the United States. Building from the work of Gloria Wekker and given my positionality, I am interested, “in the landscape that underlies the question, the cultural archive, and what it tells us about the continuities of the imperial construction of a dominant white Dutch self”(2016: 74). The personal, poetic aspects of this work engage the practices and experiences which have led me to where I am both in my professional and personal life. These aspects of my life within and beyond the academy allow me to examine histories critically and consider my entanglements with whiteness and within the matrix of coloniality of power through ekphrastic poetry.